Cam morphology in young male football players mostly develops before proximal femoral growth plate closure: a prospective study with 5-yearfollow-up. Issue 9 (15th October 2018) - van Klij, Pim; Heijboer, Marinus P; Ginai, Abida Z; Verhaar, Jan A N; Waarsing, Jan H; Agricola, Rintje
Abstract : Objectives: Cam morphology is not completely understood. The aim of this study was threefold: (1) to investigate if cam morphology development is associated with growth plate status; (2) to examine whether cam morphology continues to develop after growth plate closure; and (3) to qualitatively describe cam morphology development over 5-year follow-up. Methods: Academy male football players (n=49) participated in this prospective 5-year follow-up study (baseline 12–19 years old). Anteroposterior and frog-leg lateral views were obtained at baseline (142 hips), 2.5-year (126 hips) and 5-year follow-up (98 hips). Cam morphology on these time points was defined as: (A) visual scores of the anterior head-neck junction, classified as: (1) normal, (2) flattening, and (3) prominence; and (B) alpha angle ≥60°. Proximal femoral growth plates were classified as open or closed. Cam morphology development was defined as every increase in visual score and/or increase in alpha angle from <60° to ≥60°, between two time points. This resulted in 224 measurements for cam morphology development analysis. Results: Cam morphology development was significantly associated with open growth plates based on visual score (OR: 10.03, 95% CI 3.49 to 28.84, p<0.001) and alpha angle (OR: 2.85, 95% CI 1.18 to 6.88, p=0.020). With both definitions combined, cam developed in 104 of 142 hips during follow-up. Of these 104 hips, cam developed in 86 hips (82.7%) with open growth plate and in 18 hips (17.3%) with a closed growth plate. Cam morphology developed from 12 to 13 years of age until growth plate closure around 18 years. Conclusion: Cam morphology of the hip is more likely to develop with an open growth plate.